2021
DOI: 10.1002/jbio.202100282
|View full text |Cite
|
Sign up to set email alerts
|

Toward the development of portable light emitting diode‐based polarization spectroscopy tools for breast cancer diagnosis

Abstract: A robust, affordable and portable light emitting diode‐based diagnostic tools (POLS‐NIRDx) using a polarization‐sensitive (linear as well as circular polarization) technique were designed and developed to quantify the degree of linear polarization (DOLP), degree of circular polarization (DOCP). The study was performed on malignant (invasive ductal carcinoma) and adjacent normal ex‐vivo biopsy tissues excised from N = 10 patients at the operating wavelengths of 850 and 940 nm. The average DOLP and DOCP values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…11 Bickel et al 12 demonstrated that polarization in light scattering could be used as an effective tool in biological study. Various biological tissues, including tissues from cardiac muscle, brain, liver, kidney cortex, loin muscle, and tendon of pigs, [13][14][15][16] tissues from heart, brain, retina, kidney, and spleen of rats, 17 cardiac tissues of Lewis rats, 18,19 human breast cancer tissues, [20][21][22] and invasive breast cancer specimens, [23][24][25] have been characterized using a wide variety of optical modalities such as polarimetric light microscopy (PLM), [23][24][25] linear polarization spectroscopy, [23][24][25] Mueller polarimetry, 26 near-infrared spectroscopy (NIRS), [20][21][22]27 and optical coherence tomography (OCT). 13,14 Sprenger et al 23 devised a quantitative approach for assessing the tumor's stroma ratio by combining PLM and linear polarization in breast cancer specimens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Bickel et al 12 demonstrated that polarization in light scattering could be used as an effective tool in biological study. Various biological tissues, including tissues from cardiac muscle, brain, liver, kidney cortex, loin muscle, and tendon of pigs, [13][14][15][16] tissues from heart, brain, retina, kidney, and spleen of rats, 17 cardiac tissues of Lewis rats, 18,19 human breast cancer tissues, [20][21][22] and invasive breast cancer specimens, [23][24][25] have been characterized using a wide variety of optical modalities such as polarimetric light microscopy (PLM), [23][24][25] linear polarization spectroscopy, [23][24][25] Mueller polarimetry, 26 near-infrared spectroscopy (NIRS), [20][21][22]27 and optical coherence tomography (OCT). 13,14 Sprenger et al 23 devised a quantitative approach for assessing the tumor's stroma ratio by combining PLM and linear polarization in breast cancer specimens.…”
Section: Introductionmentioning
confidence: 99%
“…29 Also, the use of polarized light to probe the tissue has been proved to be a quick and effective way for non-invasive tissue diagnostics. 30 Kamal et al 22 designed a small, inexpensive, and easy-to-use system (POLS-NIRDx) for performing polarization-sensitive NIRS to distinguish between the malignant and the adjacent normal formalin-fixed breast biopsy tissues by quantifying the degree of linear polarization (DOLP) and degree of circular polarization (DOCP), both at 850 and 940 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation